Analyzing the relationship between foreign direct investment, trade openness and small and medium enterprise growth: Time series evidence from Vietnam (1991–2023) - Giang, Le Thi; Anh, Nguyen Tran Tu; Loan, Nguyen Thi Cam (Journal of Social Economics Research, 2025)
SMEs (Small and Medium Enterprises), accounting for more than 97% of enterprises in Vietnam, play a pivotal role in driving socio-economic progress. This paper explores how foreign direct investment (FDI) and trade openness (TO) influence SME development, drawing on annual data for the period 1991–2023. Using secondary information from the World Bank, the General Statistics Office, and the Ministry of Planning and Investment, two multiple regression models are constructed to analyze the effects of FDI and TO on the population of SMEs and their aggregate revenue. Results indicate that FDI and TO jointly explain 98.9% of the variation in SME numbers and 98.2% of SME revenue. Specifically, a 1 billion USD increase in FDI is associated with an additional 25,942 SMEs, while a 1 percentage point rise in TO corresponds to 1,832 more SMEs, both confirmed at the 1% significance level. Concerning revenue, each 1 billion USD in FDI raises SME revenue by approximately 8.273 billion USD, and each 1% increase in TO contributes about 1.062 billion USD, also confirmed at the 1% significance margin. These findings underscore the complementary roles of FDI and TO in fostering SME expansion and performance. The study recommends targeted FDI attraction policies, capacity-building programs for SMEs to integrate into global value chains, and balanced trade liberalization to sustain long-term SME growth in Vietnam.